2010
DOI: 10.1111/j.1365-2842.2010.02130.x
|View full text |Cite
|
Sign up to set email alerts
|

Tooth preparation for rest seats for cobalt-chromium removable partial dentures completed by general dental practitioners

Abstract: The aim of this project was to examine tooth preparations made by general dental practitioners (GDPs) for occlusal and cingulum rest seats for cobalt-chromium removable partial dentures (RPDs). Master casts and prescribed denture designs for cobalt-chromium RPDs produced by a commercial dental laboratory from impressions made by 45 GDPs across Wales were evaluated over a period of 5 months. Rest seats and associated interocclusal clearances were assessed using pre-determined criteria. A total of 68 casts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 18 publications
(23 reference statements)
0
19
0
5
Order By: Relevance
“…Recently, Rice et al. (39) reported that when rests were prescribed, only 30% of the examined master casts for cobalt chromium RPDs had signs of rest seats preparation. Basker et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Rice et al. (39) reported that when rests were prescribed, only 30% of the examined master casts for cobalt chromium RPDs had signs of rest seats preparation. Basker et al.…”
Section: Discussionmentioning
confidence: 99%
“…Schwarz and Barsby (38) found that 56% of UK dentists never or rarely prepared rest seats. Recently, Rice et al (39) reported that when rests were prescribed, only 30% of the examined master casts for cobalt chromium RPDs had signs of rest seats preparation. Basker et al (24) indicated that evidence of rest seat preparation was identified in 21% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…There is much to be gained in terms of developing student confidence in this important area prior to treating patients. Evidence from general dental practice suggests that dentists do not always complete optimum rest seat preparations prior to making RPDs, resulting in either inferior quality prostheses or adversely affecting the occlusion of patients receiving this treatment (25). In seven public (64%) and two private (50%) dental schools, undergraduate students did not routinely use a surveyor when designing their removable partial dentures.…”
Section: Discussionmentioning
confidence: 99%
“…As such, treatment strategies that consider signs and symptoms during the periodontal clinical examination of patients are important to provide adequate prosthetic planning and ensure the success of the treatment. Additionally, patient examination and prosthesis preparation should be executed correctly . The principles of treatment planning should be applied based on an individual assessment of the patient .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, patient examination and prosthesis preparation should be executed correctly. 28 The principles of treatment planning should be applied based on an individual assessment of the patient. 29 Thus, oral cavity preparation is essential to the success of an RPD after its installation.…”
Section: Discussionmentioning
confidence: 99%